Exploring large-scale interactive public illustrations - Thorn, Emily-Clare; Rennick-Egglestone, Stefan; Koleva, Boriana; Preston, William; Benford, Steve; Quinn, Anthony; Mortier, Richard (Association for Computing Machinery, 2016)
We present a research-through-design exploration of transforming large-scale public illustrations into interactive media. We collaborated with creative practitioners to extend an existing visual marker technology to support spatial and layered interaction with wall-sized images. We document how these techniques were used to design interactive illustrations and how visitors to an exhibition engaged with these. We conclude that it is feasible to combine spatial and layered interactions to attach complex narratives to public illustrations, and highlight challenges around instruction giving, sociality and repeat experiences